ANALISIS SISTEM INFORMASI AKUNTANSI PEMBELIAN DAN PENJUALAN PADA CV. TRI KENCANA CILEGON-BANTEN - Yulianto, M. Hendra; Djuharni, Darti (Widya Mandala Surabaya Catholic University, 2019)
The purpose of this study is to analyze and evaluate the implementation of accounting information system for purchases and sales in